Formation, Fusion, and Regeneration of Protoplasts from Wild-Type and Auxotrophic Strains of the White Rot Basidiomycete Phanerochaete chrysosporium - Gold, Michael H. (1983)
A preparation of two commercial enzymes was used to liberate protoplasts from 16-h-old mycelium of Phanerochaete chrysosporium. Regeneration frequencies of up to 5% were attained when the protoplasts were plated in a medium containing 10% sorbose and 3% agar. Fusion of protoplasts from different auxotrophic strains in polyethylene glycol-Ca(2+) produced heterokaryons. Separation of the heterokaryons into their constituent homokaryotic strains could be effected through protoplast release and formation of colonies on regeneration agar.